(3MGTjI GdaGVd GdYGde GdfMQjQ GdeObb eMeO HGbQ GdHgHgGfj OGe Xdg Ydi TQM GdEQTGO ddYGde GdQHGfj GdedG CMeO GdEQOHjdj bOS SQgs - (3GdHgHgGfj, GdCSJGP GdCcHQ, GdhMjO, eMeO HGbQ Hf eMeO Cced, (B1206 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3hjOd Ydjg CjVG GdBjGJ hGdCNHGQ GdcKjQI LOG aj Gdabg GdQVhj GYde jQMec Gddg Cf cdeG HYdeg GdYHGO ef CUfGa GdUfGFY eKd GdcJGH hGdMSGH hGdJLGQI hGdfLhe hGdWH hSGFQ GdUfGYGJ (B...s
(3BNQgG (B:s
... (3Ke dG jNai Cf dcd hGMO ef GdeTJQjf Cf jSde faS GdYHO hdjS dg GdQLhY Edi GdHGFY ceG aj UhQI GYWGA GdOjI (B. (3GfJgi cdGegs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\ 49s
(3GdPQjYI (B6\440s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis